Carbon Paste Electrode Modified by Dibenzo-18-crown-6 for the Determination of Paracetamol Using Differential Pulse Voltammetry Technique - Irdhawati Irdhawati; Ni Ketut Shinta Mas Methaninditya; Anak Agung Bawa Putra (Universitas Gadjah Mada, 2023)
The fabrication, optimization and validation of measurement using a modified carbon paste electrode (CPE) with dibenzo-18-crown-6 were carried out for the determination of paracetamol in commercial products. The pH, dibenzo-18-crown-6 concentration in carbon paste, and scan rate parameters were optimized. Validation of the measurement was observed from linear concentration range, LoD, LoQ, precision, and percentage of the recovery. The result showed that the optimum pH was at 2, the optimum concentration of dibenzo-18-crown-6 in carbon paste was 0.6%, optimum scan rates were 35 mV/s for CPE, and increased to 50 mV/s using modified CPE. The linear concentration range for CPE was obtained at 10-300 µM with LoD and LoQ of 28.88 and 96.28 µM, respectively. Meanwhile, CPE modified with dibenzo-18-crown-6 gave wider linear concentration range at 1–700 µM with LoD and LoQ of 52.36 and 174.53 µM, respectively. The CPE and modified CPE had good precision, with Horwitz ratio values of less than two. The percentage of recovery for two samples with three replicates measurements was obtained (89.81 ± 1.38)% and (108.02 ± 0.42)% for samples A and B, respectively. Dibenzo-18-crown-6 modified CPE was used for the determination of paracetamol in both samples yielding 97–98% compared with the paracetamol composition on its labels.